(3CHjGJ CdZGR hCLhHJgGs
(3ChdgG (B:s
(3HhQjf Whdi Ydi GdCjGe hGaJNQi Ydi GdeeGdc ef TGe hef jef s
(3BNQgG (B:s
(3agh eaJGM dJNdjU GdPi de jMdhG ef eHGjfg GdYbO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3NRGfI Bd HGTf CYjGf GdHUQI (B(26 (3C(B) s
Keywords: (3GdeLGejYs